A Discourse of Capital Punishment in the Islamic Law and Human Rights Law - Muhammad Eko Saputro; Andhika Febriansyah; Faradisya Diandra Putri (Contemporary Issues on Interfaith Law and Society, 2023)
Capital punishment remains a contentious issue at the intersection of Islamic law and human rights law. This paper undertakes a comprehensive examination of the discourse surrounding capital punishment within these two legal frameworks. Islamic law, rooted in the Quran and Sunnah, provides guidance on criminal justice, including provisions for the death penalty in certain cases. Human rights law, on the other hand, emphasizes the protection of individuals' inherent dignity and right to life, often challenging the legitimacy of capital punishment. Through a comparative analysis, this paper explores the philosophical, theological, and legal underpinnings of capital punishment in Islamic law and human rights law. It delves into the historical evolution of capital punishment in Islamic jurisprudence and examines contemporary interpretations and applications of hudud punishments. Additionally, it scrutinizes international human rights instruments and jurisprudence, evaluating the compatibility of capital punishment with principles of human dignity and the right to life. Furthermore, this paper examines the practical implications of capital punishment within Islamic legal systems and its interaction with human rights norms. It considers case studies and legal precedents from various jurisdictions to illustrate the complexities and challenges inherent in reconciling Islamic legal principles with international human rights standards regarding capital punishment. By engaging in this discourse, the paper aims to foster a nuanced understanding of the tensions and harmonies between Islamic law and human rights law concerning capital punishment. It contributes to scholarly dialogue on the intersection of religion, law, and human rights.